1987
DOI: 10.1002/chin.198733061
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Enthalpies of Combustion of D‐Ribose and 2‐Deoxy‐D‐ribose

Abstract: 061ChemInform Abstract (at 298.15 K -(2349.47 ±0.95) and -(2527.39 ±0.98) kJ/mol, resp.; standard enthalpy of formation -(1047.23 ±1.66) and -(869.31 ±1.68) kJ/mol, respectively).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…This value is found superior compared to other work by several authors (Table I) except the work carried out by Rahman et al 16 who reported EMI-SE of ∼60 dB at 50 phr (part per hundred part of resin) of carbon black (CB) in a blend of ethylene vinyl acetate (EVA) and acrylonitrile-butadiene copolymer (NBR) for 5 mm thick sample. However, there are several reports 30,31 indicate that high loading of CB degrades the mechanical properties of polymer. In addition to degradation of mechanical properties, such a high thickness (5mm) of the material is not commercially viable for some applications where 2-3 mm thickness is preferred.…”
Section: S E R = 10 Log(1−r) and S E A = 10 Log[t /(1−r)]mentioning
confidence: 99%
“…This value is found superior compared to other work by several authors (Table I) except the work carried out by Rahman et al 16 who reported EMI-SE of ∼60 dB at 50 phr (part per hundred part of resin) of carbon black (CB) in a blend of ethylene vinyl acetate (EVA) and acrylonitrile-butadiene copolymer (NBR) for 5 mm thick sample. However, there are several reports 30,31 indicate that high loading of CB degrades the mechanical properties of polymer. In addition to degradation of mechanical properties, such a high thickness (5mm) of the material is not commercially viable for some applications where 2-3 mm thickness is preferred.…”
Section: S E R = 10 Log(1−r) and S E A = 10 Log[t /(1−r)]mentioning
confidence: 99%